(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
Currently, due to the rapid development of the construction industry, the demand for concrete and reinforced concrete structures made using portland cement is increasing. In this regard, one of the priority tasks of the building materials production industry is aimed at modernizing production technologies, improving the quality of manufactured products, and increasing their durability, using chemical additives in the production of concrete and reinforced concrete structures, without reducing their strength.